Implementation of the Canva Media-Based Contextual Teaching and Learning (CTL) Model to Improve Arabic Vocabulary - Laily Khoirum Marzuqoh; Inayah Inayah; Waesama-ae Waemamu (Didaktika: Jurnal Kependidikan, 2026)
This research is based on the urgency of learning media innovation in helping students overcome challenges in mastering Arabic vocabulary. It aims to implement the Canva-based Contextual Teaching and Learning (CTL) model and measure its effectiveness in improving vocabulary mastery. The method used was quantitative, involving a pre-experimental design with a one-group pre-test and post-test, with a sample of 34 students in class X.2 (Olympic) at MAN 1 Kota Semarang. Results showed that the Canva-based CTL model was both effective and engaging, as the learning material was integrated into visualizations relevant to real-world situations. Statistically, this effectiveness was confirmed through the Wilcoxon Signed-Rank Test with a Z value of -5.090 and a significance level (Asymp. Sig. 2-tailed) below 0.001. Since the significance value < 0.05, H0 was rejected, and H1 was accepted, confirming that the Canva-based CTL model significantly improves students' Arabic vocabulary.